Administrative regime of vaccines - Chotova, Elena (Law Journal of New Bulgarian University, 2022)
Thе article examines the historical emergence and development of vaccines as a mass administrative law practice. It discusses the regulation of the vaccines in the frames of the Administrative law and in particular the stages of its approval. It also discusses the issues concerning the Bulgarian administrative regimes for vaccine approval and the preliminary, ongoing and subsequent control over their introduction and use.